The influence of CSR, independent commissioners, and managerial ownership on tax avoidance with asset growth as moderating variable - Mahmudi, Arsalan; Lismawati, Lismawati (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to determine the influence of corporate social responsibility, independent commissioners, and managerial ownership on tax avoidance with asset growth as a moderating variable. The number of samples in this research was 47 banking companies listed on the Indonesia Stock Exchange from 2018 to 2022, resulting in 235 observations. The research data source is the annual financial report obtained from the bank’s official website. This research uses multiple linear regression methods to show that corporate social responsibility, independent commissioners, and management ownership can influence tax avoidance. The results of the moderation test show that asset growth only moderates the influence of independent commissioners on tax avoidance, while asset growth cannot moderate the influence of corporate social responsibility and managerial ownership on tax avoidance.